The Influence of Emotional Intelligence and Motivation on the Learning Outcomes of Islamic Religious Education (PAI) for Students at SMKS Mitra Bhakti, Bandar Sribhawono District, East Lampung Regency - Elsya Febriani; Endang Sukesih; Nur Hayati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
One indicator of success in achieving educational goals can be seen from student learning outcomes while participating in learning and learning activities at school. Student achievement in their learning outcomes cannot be separated from the various factors that influence learning itself. Factors that affect student learning outcomes include internal factors and external factors. Internal factors are one of the factors that come from within students because in the teaching and learning process students are the main target. This research is a quantitative study with the type of ex-post facto research that aims to determine whether there is an effect of emotional intelligence and learning motivation on learning outcomes in Islamic religious education. Data were obtained by observation, questionnaire and documentation. The findings are: First; from the results of hypothesis testing it is known that the regression coefficient of emotional intelligence and learning outcomes obtained the regression equation Y = 34.174+ 0.520 X. Second, learning motivation has a significant effect on PAI learning outcomes. From the results of hypothesis testing, the equation Y = 38.067 + 0.493X is obtained. Third emotional intelligence and learning motivation together have a significant effect on learning outcomes PAI students of SMKS Mitra Bhakti Bandar Sribhawono. From the results of multiple linear regression calculations (double) obtained equation ȳ= =25.306+ 0.406X1+ 0.250 X2 . The constant 25,306 describes the amount of learning outcomes if influenced by emotional intelligence and learning motivation. The regression coefficient b1 of 0.406 describes the magnitude of the increase in learning outcomes, if accompanied by emotional intelligence variables, while the regression coefficient b2 of 0.250 describes the magnitude of the increase in learning outcomes if accompanied by learning motivation.